2006
DOI: 10.1007/bf02893457
|View full text |Cite
|
Sign up to set email alerts
|

Cancer gene therapy: Combination with radiation therapy and the role of bystander cell killing in the anti-tumor effect

Abstract: Current anti-cancer modalities such as surgery, chemo- and radiation therapies have only limited success in cancer treatment. Gene therapy is a promising new tool to improve outcomes. In this review, first we summarize the various strategies to kill tumor cells, and then focus on the bystander effect of gene therapy. A variety of strategies, such as gene-directed enzyme pro-drug therapy, activation of an anti-tumor immune attack, application of replication-competent and oncolytic viral vectors, tumor-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…On the other, we have also demonstrated that attenuated bystander responses occur independently of Bcl-2 overexpression in cervical cancer cells. Enhancing bystander response of tumor cells would provide a novel potential radiotherapeutic regimen where lower doses and/or smaller tumor target volume could be irradiated (Lumniczky & Safrany, 2006;Hamada et al, 2007). Azzam …”
Section: Discussionmentioning
confidence: 99%
“…On the other, we have also demonstrated that attenuated bystander responses occur independently of Bcl-2 overexpression in cervical cancer cells. Enhancing bystander response of tumor cells would provide a novel potential radiotherapeutic regimen where lower doses and/or smaller tumor target volume could be irradiated (Lumniczky & Safrany, 2006;Hamada et al, 2007). Azzam …”
Section: Discussionmentioning
confidence: 99%
“…Although direct toxicity is imparted by GDEPTmediated cell death, there is also significant growth inhibition/killing of uninfected neighboring tumor cells due to the transfer of the toxic drug. The causes of this event are hypothesized to involve transfer via gap junctions or diffusion and stimulation of an antitumor response against lysed tumor cells (Lumniczky & Safrany, 2006). Replication-defective AdV were initially used in GDEPT but demonstrated poor anti-tumor efficacy.…”
Section: Suicide Gene Therapymentioning
confidence: 99%
“…One possibility is the development of viral vectors, which can either replicate in a tumor-specific manner or the expression of the therapeutic gene is driven by tumor specific promoters. 3 Further improvement might be the design of dCK mutants, which have an increased efficiency toward gemcitabine phosphorylation. 47 …”
Section: -31mentioning
confidence: 99%
“…Malignant gliomas are among tumors considered relatively radioresistant. 1,2 One possible way to overcome tumor radioresistance is to use a gene directed enzyme prodrug therapy (GDEPT) approach, 3 where the prodrug is a radiosensitizing chemotherapeutic agent.…”
Section: Introductionmentioning
confidence: 99%